What Opportunities Exist for Making the Food Supply Nutrition Friendly? A Policy Space Analysis in Mexico - Gloria Cervantes; Anne-Marie Thow; Luis Gómez-Oliver; Luis Durán Arenas; Carolina Pérez-Ferrer (Kerman University of Medical Sciences, 2022)
Background  As part of a global policy response for addressing malnutrition, food system actions have been proposed. Within food system interventions, policies directed to supply chains have the potential to increase the availability and affordability of a healthy diet. This qualitative study aimed to identify opportunities to integrate nutrition as a priority into the food supply policy space in Mexico.Methods  Data were collected through analysis of 19 policy documents and 20 semi-structured stakeholder interviews. As an analytical framework, we used policy space analysis and embedded the Advocacy Coalition Framework (ACF) and the steps of the food chain of the conceptual framework of food systems for diets and nutrition.Results  Policy issues relevant to nutrition were viewed differently in the economic and agricultural sectors versus the health sector. Overall, the main policy objective related to nutrition within the economic and agricultural sectors was to contribute to food security in terms of food quantity. Nutrition was an objective in itself only in the health sector, with a focus on food quality. Our policy space analysis reveals an opportunity to promote a new integrated vision with the recent creation of an intersectoral group working on the public agenda for a food system transformation. This newer integrative narrative on food systems presents an opportunity to shift the existing food security narrative from quantity towards considerations of diet quality.Conclusion  The political context and public agenda are favorable to pursue a food system transformation to deliver sustainable healthy diets. Mexico can provide a case study for other low- and middle-income countries (LMICs) for putting nutrition at the center of food policy, despite the ongoing constraints on achieving this.